AI-Driven public relations in health communication: Evidence from India and Indonesia - Pangkam, Moti; Amir, Andi Subhan; Nugraha, Aat Ruchiat (PRofesi Humas, 2026)
Background: The rapid integration of artificial intelligence (AI) into health communication has redefined the way institutions relate to the public; However, existing studies highlight above all the technological and clinical dimensions, leaving a critical gap in understanding AI-driven public relations as a strategic tool that adapts outcomes such as trust and commitment, especially in developing countries. Purpose: This study aims to examine the influence of AI-driven public relations on public trust and engagement in health communication, as well as the mediating role of public trust, using cross-national insights from India and Indonesia. Methods: This study employed a quantitative survey design involving 320 respondents, equally distributed between India and Indonesia. Respondents were selected through purposive sampling based on their experience accessing health-related information through digital platforms involving AI-supported communication features. The pooled cross-national data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results: The results demonstrate that AI-powered public relations significantly enhance public trust and public engagement. Public trust also positively influences engagement and serves as the primary mediating mechanism linking AI-driven communication to engagement outcomes. Conclusion: These results demonstrate that the effectiveness of artificial intelligence in health communication is determined not only by its technological sophistication but also by its ability to promote relationships based on the trust of public engagement. Implications: This research expands on public relations theory, integrating AI into the realm of relational communication, highlighting the sensitive contexts of healthcare institutions working in different sociocultural settings and the importance of trust-oriented AI trust strategies.